Internal And External Factors On The Profitability Of Islamic Banks In Indonesia - Muhammad Sanusi; Zihab Zihab; Marfu’ah Marfu’ah (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to determine the determinants of the profitability of Islamic banks in Indonesia. This study uses a quantitative method of secondary data with a purposive sampling technique. The research data is a time series from January 2017 - June 2025 (102 observations), data sources OJK and Bank Indonesia. The multiple regression analysis technique uses Eviews 13 software. The results of the data analysis indicate that the NPF variable has a significant influence on the profitability (ROA) of Islamic banks in Indonesia. Meanwhile, the CAR, interest rates, and inflation variables do not have a significant influence on the profitability (ROA) of Islamic banks in Indonesia. This influence of NPF indicates that Islamic banks in Indonesia are important to pay attention to the level of risk of bad debts from customers who are provided with financing so that banks must have the ability to analyze potential losses arising from business risks, especially financing risks.